Археологічні дослідження в с. Буша Ямпільського р-ну Вінницької обл. - Косаківський, В.А.; Рудь, В.С. (Археологічні дослідження в Україні, 2009)
In the 2008 season the research on the territory of Busha village in Yampil Region of Vinnytsya Oblast were ongoing. Two trenches were laid. In the Trench 3 the remains of the pottery of the 17th—18th c. with the remains of the buildings and furnace for pottery firing were researched. In Trench 4 the materials of Trypillya (period ВІІ, СІІ), Chornoliska, Chernyakhivska cultures, and the Late Mediaeval period were discovered.